Correlação entre estrutura cariotípica e filogenia molecular em Rhipidomys (Cricetidae, Rodentia) do leste do Brasil - Thomazini, Núbia Badke (2009)
The genus RhipidomysTshudi, 1845 belonging to the tribe Thomasomyini(Ray Steadman & 1982) includes rodents with arboreal habits, nocturnal and solitary. Are small, the weight varies from 35 to 170 grams, characterized by a combination of long vibrissae, brush or tuft at thedistal tail and dark coats this on the back of their front legs (Tribe, 1996; Emmons & Feer, 1997 ). It is widely distributed ranging from east of Panama, crossing South America to northern Argentina. In Brazil are recorded in all biomes. Cytogenetic studies in this genus revealed a high karyotypic variability, with three diploid numbers 2n = 44, 48 and 50, and varying the number of autosomal arms (NFA) and the sex chromosomes, totaling 20 distinct cytotypes. The karyotypes with 2n = 44 retain most of the variation of the genus karyotype with 11 distinct complements autosomal (NFA = 46, 48, 49, 50, 52, 54, 61, 70, 74, 76 and 80). The karyotype with 2n = 48 has three distinct cytotypes (NFA = 66, 67 and 68), whereas 2n = 50 presents two different cytotypes (NFA = 70 and 71). It was suggested that these could be divided karyotypes and three groups according to the 2n and NFA group R. nitelacomposed of animals with 2n = 48/50, group R. leucodactyluswith 2n = 44 and NFA low ranging from 46 to 52, and group R. mastacalis2n = 44 and NFA high ranging from 74 to 80. This distinction was reinforced by the existence of private alleles in some of these groups. Although data from the literature suggest that the karyotype is a good tool to assist in the characterization of species Rhipidomys, and molecular studies begin to suggest how the karyotypes of Rhipidomysare phylogenetically structured, work involving karyotypic data on molecular characterization of populations are nonexistent in Rhipidomys. Accordingly, we propose to characterize the karyotypes of Rhipidomysthe number and morphology of chromosomes; propose a molecular phylogenetic hypothesis for the forms from eastern Brazil using a new molecular marker; verify that the karyotypes distinct monophyletic clades are correlated with, and test the validity Rhipidomysgroupings based on karyotype structure: group R. leucodactylus(NFAS low) and group R. mastacalis (NFAshigh). In this study we found two new descriptions of karyotypes, a karyotype with unprecedented high NFA (NFA 2n = 44 and = 72) and another with an unprecedented combination of X and Y chromosomes (2n = 44, = 50 NFA, XbYc). Adding our data to the literature we found 22 karyotypes described for the genus Rhipidomys. Karyotypes of these 22, 14 were associated with 12 of the 21 taxa recognized in Rhipidomys, and eight karyotypes are not associated with any recognized taxon. Furthermore, we identified six species of Rhipidomysrecognized and suggest the presence of two new taxa to eastern Brazil. We find evidence that vicarious barrier in the Atlantic is marked by the Jequitinhonha river, not the Doce river, as suggested in many studies. Revealed that the group with high NFA is monophyletic, while the group with low NFA is polyphyletic and paraphyletic, a fact which goes against the hypothesis of karyotypic groups. We found that there is an upward trend in the number of autosomal arms in the genre, being more karyotypic forms derived farther from the bridge probable origin of the genus in 9South America yet, it was proposed that the source of radiation occurred RhipidomysAndes and the populations of this region carry the primitive conditions of the group, as the 2n = 44 and low NFA. From this ancestral karyotype propose a model of karyotype evolution taking into account the distribution of chromosomal forms in each region